SURGICAL SAFETY CHECKLIST APPLICATION COMPLIANCE ANALYSIS BASED ON THEORY OF PLANNED BEHAVIOR IN SURGICAL PATIENT: LITERATURE REVIEWS - Kusnul Kotimah; Iis Rahmawati; Rondhianto Rondhianto (UPT Penerbitan Universitas Jember, 2023)
Background: Surgical safety checklistis a tool or system that is very important in implementing patient safety during surgery, especially in the operating room. One of the patient safety programs in central surgical installation is the application of a surgical safety checklist which is recognized as important by the surgical team in reducing postoperative mortality and morbidity and increasing patient safety. Objective: This study aims to determine compliance with filling out a surgical safety checklist based on the theory of planned behavior in the Central Surgery Installation (CSI). Method: The research method uses a literature review, by using Garuda, PubMed and Science Direct database searches. Selection of literature with manuscripts according to research topics with a cross sectional design. Results: A literature search showed that adherence in filling out the surgical safety checklist increased patient safety in Central Surgical Installation (CSI) programs and reduced surgical mortality worldwide. Conclusion:It can be concluded from this study that there is an analysis of adherence to the application of surgical safety checklists based on the theory of planned behavior for surgical patients in the Central Surgery Installation. Suggestion: The surgical team is expected to comply with and implement Standard Operating Procedures (SOP) by using a surgical safety checklist as an important tool or facility in implementing patient safety, especially in the operating room.